2009
DOI: 10.1016/j.fertnstert.2008.08.120
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic analysis of IVF follicular fluid in women ≤32 years old

Abstract: Objective To address the lack of predictors of IVF success by using proteomic biometrics. Design Experimental study of follicular fluid specimens from a prospective cohort of IVF patients. Setting Academic research laboratory and IVF program. Patient(s) Women ≤32 years old with <11 oocytes retrieved and no pregnancy were matched to women who had ≥ 11 oocytes and live birth (10 pairs). Year of cycle start and IVF down-regulation protocol were also matched. Intervention(s) Follicular fluid was separated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 47 publications
2
56
1
1
Order By: Relevance
“…In this study, the increased levels of C3 and ZAG in the COH FF suggest that the patients might have had aberrant immune and inflammatory responses during the cycle. The level of C3 in FF has been found to be lower in the women undergoing IVF-ET with a live birth than that in the women with a failed pregnancy [29]. On the other hand, a high follicular level of ZAG was associated with failed pregnancy of the women undergoing IVF-ET [14].…”
Section: Discussionmentioning
confidence: 94%
“…In this study, the increased levels of C3 and ZAG in the COH FF suggest that the patients might have had aberrant immune and inflammatory responses during the cycle. The level of C3 in FF has been found to be lower in the women undergoing IVF-ET with a live birth than that in the women with a failed pregnancy [29]. On the other hand, a high follicular level of ZAG was associated with failed pregnancy of the women undergoing IVF-ET [14].…”
Section: Discussionmentioning
confidence: 94%
“…In a similar study, Aleyasin et al [17] suggested that vitamin D deficiency had no correlation with IVF outcomes. Estes et al [18] demonstrated that proteomic analysis of follicular fluid had potential as a biomarker of good responders versus poor responders in IVF. The current study found that vitamin D in the follicular fluid was the same in the pregnant and non-pregnant groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Missmer et.al, performed a proteomic evaluation of follicular fluids through two-dimensional polyacrylamide gel electrophoresis followed by the Liquid chromatography-tandem mass spectrometry (LC-MS/MS) technique to compare between normoresponders versus poor-responders in matched pairs of IVF patients; however, samples were collected among women 32 years of age or less. In their analysis, they described 11 potential protein candidates for prediction of oocyte normal response [18]. Furthermore, Hanrieder et al, identified 73 unique proteins (significance level of 95%), including acute phase proteins [19], while using an alternative approach of bottom-up technique.…”
Section: Discussionmentioning
confidence: 99%